Application of photoelectric technology on melasma - Hua LI; Yong HAO; Hui HAN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Melasma is a skin disease where brown or pigmented patches appear on the face. Currently, it is difficult to be treated because of lower success rate and higher recurrence rate. In recent years, new methods for treatment of melasma have achieved satisfactory effects, for example, photoelectric technology which include intense pulsed light, Q-switched laser, fractional laser, picosecond laser, pulsed dye laser, radiofrequency, etc. Among them, intense pulse light, Q-switched laser and picosecond laser have higher efficacy, while other photoelectric technologies need further study for their efficacy.